Bottom‐Up versus Top‐Down Strategies for Morphology Control in Polymer‐Based Biomedical Materials. Issue 1 (15th October 2021) - Cook, Alexander B.; Clemons, Tristan D.
Abstract : The size and shape of polymer materials is becoming an increasingly important property in accessing new functions and applications of nano‐/microparticles in many scientific fields. New synthetic methods have allowed unprecedented capability for the facile fabrication of anisotropic and shape‐defined nanomaterials. Bottom‐up approaches including: emulsion polymerization techniques, amphiphile self‐assembly, and polymerization‐induced self‐assembly, can lead to polymer particles with precise dimensions in the nanoscale. Top‐down methods such as lithographic templating, and 3D printing, have increased the access to unique particle shapes. In this review, these recent developments are appraised and contrasted, with future research directions providing that focus on biomedical applications. Finally, the opportunity available for synergistic combinations of top‐down and bottom‐up fabrication approaches in realizing previously unattainable architectures and material properties is highlighted. Abstract : The current state of the art in both bottom‐up and top‐down synthetic approaches for controlling nanomaterial properties for biomedical applications is highlighted. Recent examples are explored, which combine these synthetic strategies, and an insight into how synergistic combinations of bottom‐up and top‐down approaches can result in the realization of unique material properties is provided.